The necessity of inheritance and innovation of classical acupuncture from the rising of dry needling从干针崛起看古典针灸传承与创新的必要性 - JIN(金观源), Guan-Yuan; JIN(金雷), Louis Lei; HE(何洁), Belinda Jie; JIN(金霞), Bonnie Xia (World journal of acupuncture-moxibustion, 2024)
By reviewing the historical background and the current state of dry needling (DN), including the "Anti-DN Independence" movement by the acupuncture profession in the west, this paper emphasizes that DN is acupuncture, or more precisely, a "de-meridian" style of acupuncture. Clinical applications of DN and its modern studies have seen a tremendous growth spurt during the past two decades, which suggests that the meridian theory of traditional Chinese medicine (TCM) may not be the exclusive theory to guide acupuncture. Even certain high-quality DN trials may serve as good examples for acupuncture research, such as refining the stimulation targets in acupoints, recognizing the reflex properties of acupoints known as acu-reflex points (ARPs), or establishing standardized indicators of stimulus amount while objectively assessing the needling efficacy. Like any other therapies, DN has its shares of drawbacks or limitations, which reminds that while innovating classical acupuncture, it is still necessary to inherit the valuable experience of classic acupuncture and the rational core of meridian theory. This is crucial for enhancing the efficacy of clinical acupuncture intervention including DN to broaden the treatment scope and indications of acupuncture.